Análise da diferença mínima detectável de corredores treinados: um estudo de caso - Velho, Rodrigo Baumann (2021)
Background: The just noticeable difference (JND) comes from the psychophysics, being conceptualized as the physically measurable magnitude in which a sensory stimulus can be perceived in relation to another stimulus, called the standard. This difference can be above (JND-A) or below (JND-B) from the standard stimulus or the total magnitude of both (JND-T). Determining the magnitude of these differences may indicate the individual’s perceptual accuracy. Objectives: To identify the just noticeable difference of trained male runners. Methodology: A case study was carried out, Athlete A and Athlete B, with at least two years of experience in running. Two experimental tests were carried out, the first was conducted to determine the maximum oxygen consumption and, then, individually calculate the value of 60% VO2max. Thus, this variable was used in the standard series of the second experimental test, as well as the other dependent variables linked to the moment when 60% VO2max occurred. The data are presented in a descriptive manner. Findings: In case 1, the magnitude of the JND was higher in the series above the standard for all variables analyzed (VO2, %VO2, HR, speed and PSE). In case 2, the magnitude was higher than the standard in all variables, except PSE. In both cases, the data range showed high variations. Conclusion: The participants’ perceptual acuity was identified through the use of JND, showing differences in magnitudes and a high variation in the data interval of the analyzed variables, especially in VO2.